Comparative Effectiveness of Infant Massage and Foot Reflexology on Infant Sleep Quality: An Explanatory Mixed-Methods Study - Gadilaj, Ivanie Dwi; Fitriana, Fitriana; Utami, Iis Tri (Academic Hospital Journal, 2026)
Background: Adequate sleep is essential for optimal infant growth and neurodevelopment, as approximately 75% of growth hormone secretion occurs during sleep. Sleep disturbances in infancy remain prevalent and may adversely affect physical, emotional, and neurological development. Infant massage and foot reflexology are widely used non-pharmacological interventions to improve infant sleep quality; however, comparative evidence supported by both quantitative outcomes and caregiver experiences remains limited.Objective: This study aimed to compare the effectiveness of infant massage and foot reflexology on infant sleep quality and to explore maternal perceptions of sleep changes following these interventions.Method: An explanatory mixed-methods study was conducted using a quantitative quasi-experimental two-group pretest–posttest design, followed by a qualitative descriptive approach. The quantitative phase involved 32 infants aged 1-12 months with sleep disturbances, who were allocated to an infant massage group (n = 16) or a foot reflexology group (n = 16). Infant sleep quality was assessed before and after intervention using a structured sleep quality questionnaire. Data were analysed using the Wilcoxon Signed-Rank Test and Mann–Whitney U Test (α = 0.05). The qualitative phase included in-depth interviews with seven mothers, purposively selected from both groups, and the data were analysed using thematic analysis to explain and enrich quantitative findings.Result:   Both infant massage and foot reflexology significantly improved infant sleep quality (p < 0.001). However, post-intervention sleep quality was significantly higher in the infant massage group compared to the foot reflexology group (p < 0.001). Qualitative findings revealed improvements in sleep duration and continuity, reduced fussiness before sleep, and increased maternal confidence in managing infant sleep routines, particularly among mothers whose infants received massage therapy.Conclusion: Infant massage and foot reflexology are effective non-pharmacological interventions for improving infant sleep quality, with infant massage demonstrating superior effectiveness. The integration of quantitative and qualitative findings highlights infant massage as a practical and family-centred intervention to support healthy sleep in infancy.